Vitamin D deficiency associates with γ-tocopherol and quadriceps weakness but not inflammatory cytokines in subjects with knee osteoarthritis - Barker, Tyler; Henriksen, Vanessa T.; Rogers, Victoria E.; Aguirre, Dale; Trawick, Roy H.; Lynn Rasmussen, G.; Momberger, Nathan G. (Redox biology, 2014)
Knee osteoarthritis (OA) is a degenerative joint condition and a leading cause of physical disability in the United States. Quadriceps weakness and inflammatory cytokines contribute to the pathogenesis of knee OA, and both of which, increase with vitamin D deficiency. Other micronutrients, such as vitamins C and E and β-carotene, modulate inflammatory cytokines and decrease during inflammation. The purpose of this study was to test the hypothesis that vitamin D deficiency associates with quadriceps weakness, an increase in serum cytokines, and a decrease in circulating micronutrients in subjects with knee OA. Subjects (age, 48±1 y; serum 25(OH)D, 25.8±1.1 ng/mL) with knee OA were categorized as vitamin D deficient (n=17; serum 25(OH)D≤20 ng/mL), insufficient (n=21; serum 25(OH)D 20-29 ng/mL), or sufficient (n=18; serum 25(OH)D≥30 ng/mL). Single-leg strength (concentric knee extension-flexion contraction cycles at 60 °/s) and blood cytokine, carotene (α and β), ascorbic acid, and tocopherol (α and γ) concentrations were measured. Quadriceps peak torque, average power, total work, and deceleration were significantly (all p<0.05) impaired with vitamin D deficiency. Serum γ-tocopherol concentrations were significantly (p<0.05) increased with vitamin D deficiency. In the vitamin D sufficient group, γ-tocopherol inversely correlated (r=-0.47, p<0.05) with TNF-α, suggesting a pro-inflammatory increase with a γ-tocopherol decrease despite a sufficient serum 25(OH)D concentration. We conclude that vitamin D deficiency is detrimental to quadriceps function, and in subjects with vitamin D sufficiency, γ-tocopherol could have an important anti-inflammatory role in a pathophysiological condition mediated by inflammation.